KEEFEKTIFAN MODEL DISCOVERY LEARNING BERBASIS ETHNOMATHEMATICS MATERI BANGUN DATAR TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SDN PASUCEN 02 - Uswatun Hasanah; Aries Tika Damayani; Fine Reffiane (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The purpose of this study was to determine the effectiveness of themodel discovery learning based on ethnomathematics shape of flatmaterial on the learning outcomes of 4th grade students of SDN Pasucen 02, Pati Regency. The approach used is an experimental research approach with a one group pretest-posttest design. The data analysis used included normality test, comparative test, and completeness test. The results showed that the data were normally distributed. T-test research results obtained t count 18.06> t table 1.69 with a significance level of 0.05, then Ha accepted. This means that there is a difference in the average learning outcomes of students with flat shape material between before and after using the discovery learning -based ethnomathematics. The results showed that the average test of student learning outcomes using the discovery learning -based ethnomathematics was 69.00 better than the average learning outcomes of students before using the discovery learning -based ethnomathematics, namely 40.42. The average value of student learning outcomes using the discovery learning -based ethnomathematics exceeded the KKM 65 with the proportion of students who completed 82.86%. It can be concluded that the discovery learning -based ethnomathematics is effective for learning outcomes of flat shape material for 4th grade students of SDN Pasucen 02.